“Pasos al costado”: uma história do processo de constituição das barras e a platinização do torcer no Rio Grande do Sul (2001-2011) - Oliveira, Elias Cósta de (2023)
After 60 years of samba, carnival and organized support, a new form of support was created in Porto Alegre, capital of Rio Grande do Sul. With the entry of the first platillos bass drums, coming from Buenos Aires, fans singing in Spanish and flags from Argentina and Uruguay in the stands, a new movement was consolidated in the gaucho stadiums. Based on changes in the aesthetics of material culture, new musical styles – such as cumbia villera – and new ways of singing, this investigation aims to understand the process of identification with forms of twisting of the so-called bars (2001-2011), typical of the rio platense region, and the denial of traditional forms of Brazilian supporters by some supporters in Rio Grande do Sul. The creation of Geral do Grêmio, by Grêmio Foot Ball Porto Alegrense and Guarda Popular, by Sport Club Internacional will be historicised. Our temporal cut includes the creation, consolidation and evolution of the first internal fights, when dissident groups were created. For that, several methodological procedures were used from the History of the Present Time, such as historiographical surveys, consultation in periodicals, analysis of photographs, use of podcasts about the fan culture and analysis of songs from the fans as an oral source. In this sense, we investigated channels of organized supporters and channels of the supporters themselves, whose material is available on the YouTube platform. In this way, it was possible to perceive that the creation of the barra style in RS is linked to different factors, which are related in the temporality process, such as the creation and expansion of tournaments organized by Conmebol, the increase in television broadcasts and the Grêmio team inserted in games of all international tournaments. In addition, the geographic issue stands out, which made it easier for Grêmio fans to travel to the Platine countries, since, with the approval of Mercosur, residents of the Southern Cone no longer needed to use a passport to transit between countries, facilitating fan excursions. Likewise, the violence in society in the 1990s was reflected in the gaucho fans, who were banned and/or criminalized in the stadiums, leaving a vacuum in the fan associations. From that, the bars began with Geral do Grêmio and later with the Popular Guard. These fans reinforce the feeling of gaucho pride, seeking to belong to an imagined community of the platinum region, seeking a common identity with these countries to legitimize themselves as bars, changing the dynamics of the way of cheering the main teams in the state.